(untitled) - Acquaah, George (Oxford, 2007)
Until recently, plant breeders have depended primarily on classical tools to develop new and improved products for producers and consumers. However, with the advent of biotechnology, breeders are increasingly incorporating molecular tools in their breeding work. In recognition of the current state of methods and their application, this text introduces both classical and molecular tools for plant breeding.
Keywords: Plant breeding,Plant genetic,Sự sinh sản ở thực vật,Gen thực vật